Inovasi Budidaya Azolla Sp. Sebagai Sumber Pakan Lokal Untuk Meningkatkan Efisiensi Budidaya Ikan Nila dan Ketahanan Pangan Di KUB Mundam Jaya, Kelurahan Mundam, Kecamatan Medang Kampai, Kota Dumai - Masjudi, Heri; Mulyadi, Mulyadi; Pamukas, Niken Ayu; Adelina, Adelin; Syawal, Henni; Sumiarsih, Eni; Pristiana, Aris; Aprianti, Rahma (Unri Conference Series: Community Engagement, 2025)
The Mundam Jaya Joint Business Group (KUB) in Mundam Village, Medang Kampai District, Dumai City, participated in a community service program introducing the cultivation of Azolla sp. as a local feed source to improve the efficiency of Nile tilapia farming. The program aimed to reduce production costs, enhance productivity, and strengthen food security and the local coastal economy. The methods implemented included training, field practice, mentoring, and continuous monitoring and evaluation using a learning by doing approach. The results demonstrated that group members were able to master Azolla cultivation techniques, from propagation to its application as supplementary feed for tilapia. The use of Azolla reduced dependence on commercial feed, lowered feed costs by up to 45%, and improved tilapia growth and survival rates, with survival exceeding 85%. Beyond technical outcomes, the program also enhanced participants’ business management skills, particularly in production record-keeping and marketing strategies. Overall, this initiative proved that the utilization of natural resources such as Azolla as fish feed can serve as a sustainable innovation in aquaculture. It not only supports the development of the village aquaculture sector but also contributes to economic independence and food security for coastal communities.